Aborsi dalam Perspektif Ayat-Ayat/Hadis Ahkam dan Undang-Undang Kesehatan: Studi Perbandingan - Afiati, Afa; Maspufa, Olivia Sulistya; Ekaputri, Nesya (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
Abortion is increasingly practiced among teenagers and married couples. Now people think abortion is a trivial matter, they don't think about the consequences of it. Lack of religious education and strict surveillance from the government and parents make it appear as if they are blind and deaf to the laws and sanctions for abortion. Public understanding of the law and the impact of abortion is the goal of this research both in a religious perspective and a legal perspective in Indonesia. There is also public awareness of their own health and violations of human rights. This type of research is library research, this research uses a descriptive-analytical approach and in its subject matter uses comparative analysis techniques. The results of this study state a comparison between the verses of the law and hadith ahkam as well as the health law. So between the verses of the law and the ahkam hadith that are complementary, but if both are compared with the laws and regulations in general lies in the limit of pregnancy or the age limit allowed for abortion and the similarity is broadly speaking, abortion is an act that violates the law, if done it will be sanctioned. The three points of discussion also attach importance to the health of the mother.